Metastatic Primitive Neuroectodermal Tumor Arising from Stomach: A Case Report - Yu, Song Yi; Lee, Chang-Hoon; Jeon, So-Yeon; Yhim, Ho-Young; Lee, Na-Ri; Kwak, Jae-Yong; Yim, Chang-Yeol; An, Ae Ri; Park, Ho Sung; Song, Eun-Kee (Archives of Clinical and Medical Case Reports, 2020)
Gastric primitive neuroectodermal tumor (PNET) is extremely rare and treatment of metastatic gastric PNET is not established. Herein, we report a case of a 54-year-old male who had undergone total gastrectomy with D2 lymph node dissection, distal pancreatectomy, and splenectomy for the curative intent of primary gastric PNET initially and received multimodal treatment including chemotherapy, radiotherapy, and palliative metastasectomy after recurrence and metastasis. He died 5.6 years after first diagnosis and 4.2 years after relapse due to disease progression. Although no effective chemotherapy agents and standard treatments have been determined, multimodality treatment approach applied to this patient has helped to achieve relatively long-term survival. This case report will be helpful to identify the disease progress and prognosis of gastric PNET and to know the effects of various treatment methods.